KEGELISAHAN DIRI SEBAGAI EKSPRESI DALAM KARYA SENI LUKIS - Arif Budiman, Drs. Yasrul sami, S.Sn., M.Sn., Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2018)
This work aims to visualize anxiety as an expression in abstract painting. Humans in living life can not be separated from the problems both with individuals and groups, from some problems that occur there are cause anxiety.In realizing this work requires a brilliant idea and certainly can not be separated from the stage or process of creation. In this case the stages of the process of creating paintings of self-anxiety is through the process of preparation, elaboration, synthesis, concept realization, and completion.The works are displayed with abstract painting style, to visualize the feeling arising from the anxiety that the author feels in the life of society. This picture is packed in a painting entitled: (1). Limit # 1, (2). Limit # 2, (3). Stacking over the overlay # 1, (4). Stacking over overlay # 2, (5). Sorting # 1, (6). Sorting # 2, (7). Trapped # 1, (8). Stuck # 2, (9). In Anxiety, (10). Tangled.Keywords: Anxiety, Expression, Art Painting